2017
DOI: 10.4103/ijnm.ijnm_167_16
|View full text |Cite
|
Sign up to set email alerts
|

Rectal carcinoma metastases to multiple skeletal muscles-role of f-18 FDG PET/CT

Abstract: Rectal carcinoma with metastasis to skeletal muscle is rare. So far, 16 cases of skeletal muscle metastasis from colorectal carcinoma have been documented of which only 5 were rectal carcinomas.[1] We discuss here the case of a 69-year old male, a known case of mucinous adenocarcinoma status post neoadjuvant chemoradiotherapy and abdomino perineal resection, who presented with low backache 4 months post surgery. He was found to have metastasis to multiple skeletal muscles without the involvement of common site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Prabhu et al reported a case of rectal adenocarcinoma, with biopsy-proven multiple metastases to skeletal muscles, including erector spinae and thigh muscles which were initially detected on 18F-FDG PET/CT scan. They concluded that 18F-FDG PET/CT is a useful modality for localising metastatic sites and guiding the management 9. Unsal et al also reported metastasis to forearm muscle in a 31-year-old man with a history of mucinous rectal adenocarcinoma without other sites of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prabhu et al reported a case of rectal adenocarcinoma, with biopsy-proven multiple metastases to skeletal muscles, including erector spinae and thigh muscles which were initially detected on 18F-FDG PET/CT scan. They concluded that 18F-FDG PET/CT is a useful modality for localising metastatic sites and guiding the management 9. Unsal et al also reported metastasis to forearm muscle in a 31-year-old man with a history of mucinous rectal adenocarcinoma without other sites of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, skeletal muscle metastases are asymptomatic and are diagnosed incidentally on imaging such as MRI, CT scan and positron emission tomography (PET)/CT scan 7. Colorectal carcinomas are second and third most common cancers among men and women, respectively,9 with 50 260 deaths from the disease in 2017 in the USA 10. Most common metastatic sites for these tumours include liver, lung and peritoneum 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 There are several mediators such as tumor necrosis factor-α, transforming growth factor-β, lymphocyte infiltrating factor, interferon-γ, lactic acid, and plasminogen activator inhibitor that are released by muscle cells and exert an inhibitor effect on the growth of several tumor cell lines. 12 Skeletal muscle metastasis often means there is an underlying widespread pathology, which correlates to a poorer prognosis. The prognosis of patients with skeletal muscle metastases is variable from benign to poor depending on the primary tumor and disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…11 There are several mediators such as tumor necrosis factor-α, transforming growth factor-β, lymphocyte infiltrating factor, interferon-γ, lactic acid, and plasminogen activator inhibitor that are released by muscle cells and exert an inhibitor effect on the growth of several tumor cell lines. 12…”
Section: Discussionmentioning
confidence: 99%